KAJIAN AKIFER DI KECAMATAN DENPASAR BARAT PROVINSI BALI - Suyarto, R. (Bumi Lestari; Vol 12 No 1 (2012), 2012)
Denpasar city which is the center of the development requires a quite a lot of water. Intensively the taking of groundwater can lead to changes in soil structure or water cycle and environmental damage. The aims of this study are to examine aquifer as a water carrier layer that that spread laterally and vertically. Aquifer analysis performed by analysis of aquifer parameters from well bore data. West Denpasar District is a centralized location of underground water flow to the sea, because of this the region has a high potential for groundwater discharge which values >10 liters/second. Generally, augmentation of ground water from rainfall that is equal to 1.528 liters/second. Data from well bore indicate good water carrier layers (tuffs, sand, gravel) are at more than 20 m depths, there is free ground water from a depth of 12 m but with a small discharge. After 20 m depth, there is a new semi-free aquifer until more than 24 m depths. Well bore in the Mahendradata Street showed groundwater discharge is moderate with value 8.467 liters/second. In this well bore two types Aquifer types was found there are unconfined aquifer and Semi-confined aquifer. Unconfined aquifer located on the surface of the rock layers. Therefore, Semi-confined aquifer is more dominant because the layers are rare waterproof that located in Palasari formation layer. The aquifer layer was also found in the relative position of more than 30 m from the local surface.
Keywords: aquifer; ground water; rock formation